2003
DOI: 10.1074/jbc.m307556200
|View full text |Cite
|
Sign up to set email alerts
|

Serine/Threonine Kinase Mirk/Dyrk1B Is an Inhibitor of Epithelial Cell Migration and Is Negatively Regulated by the Met Adaptor Ran-binding Protein M

Abstract: Minibrain-related kinase (Mirk)/Dyrk1B is an arginine-directed serine/threonine kinase that is active in skeletal muscle development but is also expressed in various carcinomas. In the current study, the Met adaptor protein Ran-binding protein M (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 42 publications
4
66
0
4
Order By: Relevance
“…Mv1Lu cells growth arrest in G 0 /G 1 in response to transforming growth factor-␤1 or to culture in serum-free conditions, whereas treatment with a cellular mitogen releases this arrest (15). In addition, we recently have made a stable Mirk-inducible subline from Mv1Lu cells and have shown that the induction of Mirk inhibited the migration of these cells in wounding experiments and inhibited their invasion through polycarbonate Transwell filters (12). Therefore, we know that Mirk exhibits biological activity in these epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mv1Lu cells growth arrest in G 0 /G 1 in response to transforming growth factor-␤1 or to culture in serum-free conditions, whereas treatment with a cellular mitogen releases this arrest (15). In addition, we recently have made a stable Mirk-inducible subline from Mv1Lu cells and have shown that the induction of Mirk inhibited the migration of these cells in wounding experiments and inhibited their invasion through polycarbonate Transwell filters (12). Therefore, we know that Mirk exhibits biological activity in these epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, transient overexpression of Mirk in epithelial cells blocked cells in G 0 /G 1 . In earlier studies, we had made a stable Mirk-inducible subline from nontransformed Mv1Lu lung epithelial cells (12). The induction of Mirk caused a 30 -40% inhibition of Mv1Lu cell entry into S phase as measured by decreased uptake of [ 3 H]thymidine (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jab1 functions as an adaptor between CRM1 and p27 (23). The Mirk-containing nuclear complexes have not been completely characterized, but we found in an earlier study that they do not contain Jab1 (22), which is found within the 450-kDa signalosome and smaller complexes (22,23).…”
mentioning
confidence: 91%
“…Possibly Mirk and p27 occupy a different part of the nucleus than CRM1 during G 0 . Mirk is found in 670-kDa complexes within the nucleus together with the Ran-binding protein RanBPM (12,22). Jab1 functions as an adaptor between CRM1 and p27 (23).…”
mentioning
confidence: 99%